Let It Go: Multicultural Society in Los by Tom Naegels - Pareit, Timothy (Werkwinkel, 2018)
Although scholars in the Netherlands have already attempted to integrate literary theories on migration with the specific Dutch context, none such attempts have so far been made for Flemish literature. The current paper therefore scrutinises the novel Los by Tom Naegels, an (autobiographical) account of the riots in Borgerhout (Antwerp) after the murder on Islam teacher Mohamed Achrak in 2002. As the author also covered these events as a journalist, the analysis investigates the manner in which this topical matter is intertwined with the more personal story about the struggle conducted by Naegels’s grandfather for euthanasia. The paper leans on Jérôme Meizoz’s posture theory, which differentiates the author figure from the biographical person and the narrator. In addition, the novel is situated within the contemporary literary return towards realism and Flemish literature’s negotiation of Flemish identity. By focussing on these three elements – the theme of migration, realism and Flemish identity – the paper attempts to contribute to the development of a literary theory on migration in Flanders.